PENGARUH INFRASTRUKTUR, INDEKS PEMBANGUNAN MANUSIA DAN KORUPSI TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI INDONESIA - Defianti, Lusi; Aimon, Hasdi; Alianis, Alianis (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract:This research aims to determine the effect of (1) infrastructure andhuman development index on economic growth in Indonesia, (2) humandevelopment index and corruption on community’s prosperity in Indonesia, (3)economic growth on the prosperity of the community in Indonesia by using thesimultaneous equation method with the Indirect Least Square Model and paneldata from 2014 to 2018. The estimates of this research show that (1) theinfrastructure has no significant effect on economic groeth in Indonesia (2) thehuman development index has a positive significant effect on economic growth inIndonesia (3) the human development index has a positive significant effect onthe prosperity of community in Indonesia (4) the corruption does not have asignificant effect on the prosperity of community in Indonesia (5) the economicgrowth has a positive significant effect on the prosperity of community inIndonesia.Keyword : Prosperity of Community, Economic Growth, Infrastructure,Human Development Index, Corruption